Sensitivity of Corynespora cassiicola from soybean to carbendazim and prothioconazole - Xavier,Sheila A. (2013)
The incidence of target spot disease on soybean has increased in recent years in Brazil even with intensive use of fungicides, and fungal resistance has been reported in recent studies. The objective of this study was to determine the fungicide sensitivity to carbendazim and prothioconazole in a sample of 24 isolates of Corynespora cassiicola from soybean collected from 1996 to 2011 in the states of Paraná, Mato Grosso and São Paulo ( Brazil) and Corpus Christi (Paraguay). The 50% effective concentration (EC50) values were estimated by the relative mycelium growth reduction on fungicide-amended medium with the doses of 0, 0.5, 1, 10, 100 and 1000 µg of active ingredient/ mL. For carbendazim, four highly resistant isolates (EC50>50 µg/mL) were observed from samples collected from Mato Grosso in 2008 and from Paraná and Mato Grosso in 2011. The EC50 values for prothioconazole ranged from 0.47 µg/mL to 26.44 µg/mL (mean: 5.02 µg/ ml). The results reinforce the occurrence of C. cassiicola resistance to benzimidazole in Paraná and Mato Grosso states.